Estimating the effect of death penalty moratoriums on homicide rates using the synthetic control method - Oliphant, Stephen N. (Criminology & public policy, 2022)
Research Summary Research examining death penalty deterrence has been characterized as inconclusive and uninformative. The present analysis heeds a recommendation from prior research to examine single-state changes in death penalty policy using the synthetic control method. Data from the years 1979-2019 were used to construct synthetic controls and estimate the effects of death penalty moratoriums on homicide rates in Illinois, New Jersey, Washington, and Pennsylvania. Moratoriums on capital punishment resulted in nonsignificant homicide reductions in all four states. Policy Implications Inconsistent with a deterrence hypothesis, no evidence of a deterrent effect attributable to death penalty statutes was found. Given the gravity and finality of state-sanctioned execution, it is important that policy makers consider the weight of evidence of the death penalty's capacity to deter, as well as issues of equity, justice, and fairness, in their decision making about death penalty policy.